The emerging one-stop shop in agricultural value chains: Agro-input retailers in Myanmar - Goeb, Joseph; Minten, Bart; van Asselt, Joanna; Reardon, Thomas; Aung, Zin Wai; Htar, May Thet (International Food Policy Research Institute, 2025)
With the intensification and modernization of agriculture in Myanmar, farmers are increasingly dependent on purchased agro-inputs—such as seeds, fertilizers, and pesticides—to enhance productivity. These inputs are typically acquired from small and medium-sized agro-input retailers. Despite their growing significance in agrifood value chains, limited research has examined the roles these retailers play. Drawing on large-scale, nationwide surveys of farmers and agro-input retailers in Myanmar, we explore their operations and implications in this context. Key findings include: 1. There is widespread and increased use of agro-chemicals in Myanmar. Among dry season crop farmers, pesticides were the most commonly purchased input, reported by 73 percent of respondents, closely followed by fertilizers at 72 percent. While fertilizer usage has remained relatively stable compared to nearly a decade ago (75 percent in 2016), pesticide use has increased significantly—rising by 13 percentage points since 2016. 2. The expansion of pesticide use is reflected in official data. In 2017, just over 500 pesticide products were registered; by 2024, this number had increased eightfold. Similarly, pesticide imports in 2023 were five times higher than in 2013. 3. Many agro-input retailers provide complementary services beyond product sales, offering services such as credit, agricultural extension advice, mechanization facilitation, transportation, crop buying, and emergency loans. These complementary services integrate them more deeply into agricultural value chains. 4. Only 12 percent of retailers provided none of the aforementioned complementary services, while 16 percent offered four or more. Competition is a driver of service provision—retailers located near competitors are more likely to offer extension and credit services. 5. Retailers in insecure areas are equally engaged in delivering complementary services as those in more secure regions. 6. Agro-input retailers are a vital source of credit, with nearly half of the farmers purchasing inputs on credit—typically at a monthly interest rate of 2 percent. Larger farmers are more likely than smaller ones to access credit through retailers. 7. Nearly half of the farmers reported receiving agricultural extension advice from their main retailer. This advice often pertains to retailer-sold products but can also address broader agronomic issues. Larger farmers are more likely to use these services than smaller ones. Given the limited availability of public extension services in Myanmar, agro-input retailers are an important, yet often overlooked, source of agricultural knowledge. 8. Despite their advisory role, farmers generally trust retailers’ advice less than other sources. Trust in agro-input retailers ranks below that in other farmers, public, and private extension agents, and only above trust in mills. Notably, medium and large farmers exhibit higher relative trust in retailers compared to smaller farmers. 9. Policy Implications: • The rapid increase in pesticide use by farmers in the country raises a number of health, safety, and environmental concerns, especially in a situation where oversight is limited given insecurity and travel concerns. • The decline in public agricultural service delivery, such as extension and credit, in the country also underscores the need for increased attention from stakeholders focused on agricultural productivity and equity. • While agro-input retailers play crucial, multifaceted roles, their services are not universally accessible. Over-reliance on private providers may risk marginalizing smaller farmers from critical services like credit. • The dependence on retailers for extension advice raises concerns about accessibility and credibility. Low trust in retailer-provided information may hinder behavior change and contribute to product misuse, especially regarding inputs with health and environmental risks like pesticides. • Further research is needed to understand the nature and impact of the advice given by private retailers. Complementary policy efforts—such as training, certification programs, and trust-building initiatives—may help enhance service quality and farmer confidence.